1989
DOI: 10.1210/jcem-68-4-707
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid and Goitrogenic Effects of Millet: Role of C-Glycosylflavones*

Abstract: Pearl millet [Pennisetum millet (L.) leeke] is the main source of food energy for the rural poor in many areas of the semiarid tropics. Epidemiological evidence suggests that millet may play a role in the genesis of endemic goiter in these areas, and sparse experimental data in rats support this suspicion. This study was undertaken to determine in vivo in rats and in vitro using porcine thyroid slices and a thyroid peroxidase (TPO) assay the goitrogenic and antithyroid effects of millet diets, extracts of mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 15 publications
4
67
0
Order By: Relevance
“…Our results of the goitrogenic effects of p-coumaric acid are in harmony with previous reports for p-coumaric acid-related compounds. Certain flavonoids (hesperidin, hesperetin, catechin, and phloretin) are known to have intrinsic antithyroid activity [6,16]. Moreover, flavonoid metabolites such as resorcinol, phloroglucinol, and dihydroxybenzoic acid have antithyroid activity [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Our results of the goitrogenic effects of p-coumaric acid are in harmony with previous reports for p-coumaric acid-related compounds. Certain flavonoids (hesperidin, hesperetin, catechin, and phloretin) are known to have intrinsic antithyroid activity [6,16]. Moreover, flavonoid metabolites such as resorcinol, phloroglucinol, and dihydroxybenzoic acid have antithyroid activity [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that feeding of both unfermented and fermented millet to rats were associated with similar changes on thyroid follicles size or on thyroid hormone profile. On the contrary, we [4] recently showed in rats that traditional fermentation of one millet cultivar (Balady) clearly potentiated its goitrogenicity and induced an increase in serum T 3 , whereas traditional fermentation of another millet cultivar (Bayoda) caused an increase in both serum T 4 and T 3 .…”
Section: Introductionmentioning
confidence: 91%
“…Subsequent investigations have shown that feeding of millet diets to rats resulted in an enlargement of the thyroid gland and/or distortion of thyroid hormone profile [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The thyroid gland is responsible for the production of hormones involved in regulating metabolism, body weight and oxygen requirement as well as normal growth and development during childhood. The thyroid hormones (tri-iodothyronine (T 3 ) and thyroxine (T 4 ) are synthesized in the gland from iodine and the amino acid tyrosine [4][5][6]. At the molecular and biochemical levels, isoflavones have the ability to change thyroid cell events in at least two ways.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, by interaction with thyroid binding globulin (TBG). This is a plasma protein involved in the inactivation and transport of T 3 and T 4 . It has been hypothesized that phytoestrogens could potentially increase TBG concentrations.…”
Section: Introductionmentioning
confidence: 99%